Parallel resolution of triangular systems - Rodríguez González, Ihosvany (2020)
The resolution of triangular systems is a computational nucleus widely used in various scientific applications. This research performs the implementation and comparison of several parallel algorithms against an efficient sequential algorithm for solving triangular systems. The algorithms are distinguished by the way of partitioning the matrix and the allocation to the processors. The analysis of the behavior of the algorithms is performed in the solution of systems of linear superior triangular equations in a cluster of computers. For this, the arithmetic time, communication time, speed-up, and maximum efficiency metrics are taken into account. Experiments were performed for each algorithm with different matrix sizes on various processors. The algorithm with the best results was the one that blocks the rows of the matrix and applies a cyclical distribution in the cluster.